Employee performance analysis of Paul Bakery Restaurant in Jakarta during the COVID-19 pandemic by measuring leadership, motivation and compensation through job satisfaction - Budiono, Aris (Turyzm/Tourism, 2022)
The purpose of this study is to analyze the influence of leadership, compensation and motivation, by using job satisfaction as an intervening variable, on employee performance during a crisis in the context of a company in the restaurant service sector. A tiered linear regression with two models was used: Model 1 analyzed the influence of leadership, compensation and motivation on job satisfaction while Model 2 explored the impact of leadership, compensation, motivation and job satisfaction on performance. The results showed that leadership, compensation, and motivation, simultaneously and partially, had a significant effect on job satisfaction. While together they had a substantial impact on performance, but only partially on leadership and compensation do not affect performance. There is however an indirect effect of leadership and compensation variables on performance through job satisfaction. In comparison, the motivation variable does not affect either directly or indirectly